Robust profiling of microRNAs and isomiRs in human plasma exosomes across 46 individuals - Karlsen, Tommy A. (Sci Rep, 2019)
microRNAs (miRNAs) are small double stranded RNA molecules consisting of two complementary strands called the 5p and 3p arms. Following imprecise processing and/or addition of nucleotides at the ends, miRNA biogenesis can give rise to variants called isomiRs. Exosomes are small vesicles released by cells. They have attracted attention due to their potential use in biomarker development because of their content of biomolecules, including miRNAs and isomiRs. Exosomes are found in body fluids such as plasma. In this study we used next generation sequencing to investigate the distribution of 5p and 3p arms of both miRNAs and isomiRs in plasma exosomes from 46 individuals. Among the canonical miRNAs there was similar prevalence between 5p and 3p miRNAs. Most of the miRNAs had isomiRs, and in approximately half of the cases an isomiR was more abundant than the corresponding canonical miRNA. Most of the isomiRs were generated from 5p miRNAs. There were very small differences in the concentration of canonical miRNA and isomiR sequences between donors, suggesting tight control of isomiR generation and sorting into exosomes. IsomiRs are abundant in plasma exosomes and should be included in analysis when plasma exosomal miRNAs are investigated as potential biomarkers for disease development.